Rational theories of the future in general equilibrium models - Burnell, Stephen (School of Management Working Papers, 1990)
This paper focusses upon three particular models - the basic Arrow-Debreu model, a simple model with two trading dates and asset markets, and the overlapping generations model - and looks at the theories of the future agents must hold in a rational expectations equilibrium. Not suprisingly, many of the difficulties of general equilibrium theory can be rephrased by asking: How could agents ever come to hold correct theories of the future?